Devising the recipe for a cake with fresh sliced pumpkin according to culinary quality indicators - Liubych, Vitalii; Novikov, Volodymyr; Zheliezna, Valeriia; Prykhodko, Vitalii; Balabak, Oleksandr; Kirian, Viktor; Tryhub, Oleh; Bardakov, Volodymyr; Kyrpa, Mykola; Petrenko, Vasyl (Eastern-European Journal of Enterprise Technologies, 2022)
This paper considers the influence of different quantities and shapes of fresh sliced pumpkin on the culinary quality of a cupcake. A change in the culinary quality of the cupcake depending on the amount of sliced pumpkin has been established. It was found that the cupcake’s surface color and crumb depended on the amount of fresh sliced pumpkin. The shape of the slice did not change these cupcake parameters. The color of the surface of the cupcake with the addition of 5‒25 % of the sliced pumpkin was at the level of control – light yellow. When adding 30‒40 % ‒ yellow; 45‒50 % ‒ dark yellow. The cupcake’s crumb color with the addition of 5‒10 % of sliced pumpkin and without it was light yellow. Adding 15‒35 % of sliced pumpkin provided for a yellow color of the crumb. With the addition of 40‒50 % of sliced pumpkin, the color was orange. The use of fresh sliced pumpkin in the amount of 25 % reliably reduces the smell and taste of the consumer evaluation of the cupcake. At the same time, the level of smell and taste was good (7 points). It should be noted that when adding 20 % fresh sliced pumpkin, the smell and taste of pumpkin in the cupcake was weak – 7 points. Social studies have been conducted and the main criteria for cupcake buyers have been established. It was found that cupcakes are in high demand and have the prospect of being enriched with pumpkin. Among the respondents, the new product had a high probability of buying. Its price is less important in this case. It was proven that its chemical composition and culinary quality are of greatest importance when choosing a cupcake. In the technology of cupcake production, it is necessary to add 20‒25 % of fresh sliced pumpkin of various shapes relative to the mass of the dough. The use of this amount of sliced pumpkin makes it possible to bake a cupcake with a light-yellow surface and yellow crumb. The consumable level of the cupcake is good while the smell and taste of the pumpkin in it is weak. The recommendations provided here could be used by small-scale grain processing enterprises when baking flour confectionery products